2021
DOI: 10.1038/s41388-021-01772-y
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant CREB1 activation in prostate cancer disrupts normal prostate luminal cell differentiation

Abstract: The molecular mechanisms of luminal cell differentiation are not understood well enough to determine how differentiation goes awry during oncogenesis. Using RNA-Seq analysis, we discovered that CREB1 plays a central role in maintaining new luminal cell survival and that oncogenesis dramatically changes the CREB1-induced transcriptome. CREB1 is active in luminal cells, but not basal cells. We identified ING4 and its E3 ligase, JFK, as CREB1 transcriptional targets in luminal cells. During luminal cell different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Moreover, qRT-PCR and Western blot assays showed that the mRNA and protein expression levels of CREB1’s target genes were downregulated in circEZH2-depleted HCT116 and SW620 cells (Additional file 10 : Fig. S3), including BCL-2, Cyclin A2, MMP-9 and GLUT3 [ 24 29 ]. RNA stability assays revealed that circEZH2 knockdown remarkably reduced the CREB1 mRNA stability in HCT116 and SW620 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, qRT-PCR and Western blot assays showed that the mRNA and protein expression levels of CREB1’s target genes were downregulated in circEZH2-depleted HCT116 and SW620 cells (Additional file 10 : Fig. S3), including BCL-2, Cyclin A2, MMP-9 and GLUT3 [ 24 29 ]. RNA stability assays revealed that circEZH2 knockdown remarkably reduced the CREB1 mRNA stability in HCT116 and SW620 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been well-established that cAMP response element-binding protein 1 (CREB1) belongs to a family of transcription factors whose activities are stimulated by increased intracellular cAMP [ 24 , 27 , 44 47 ]. Upon protein kinase A (PKA)-mediated reversible phosphorylation at serine 133 residue (Ser133ph), CREB1 can bind to DNA via a bZIP domain that recognizes cAMP response element (CRE; TGACGTCA or TGACG/CGTCA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine PC cells share a significant IL30-dependent upregulation of oncogenes, such as Abcb1a , that confers resistance to chemotherapy [ 58 ], Bcl2 , that rescues cancer cells from apoptosis and drives androgen-independent growth [ 59 ], Cav2 , which can activate cellular mitogenesis [ 60 ], and Creb1 , which regulates a network of genes required for cell survival, proliferation and migration [ 61 ]. In murine PC cells, IL30 also promotes the expression of Nfkb1 , the master regulator of immunity genes, cell-cycle modulators, survival signals, and of growth and angiogenic factors [ 62 ]; Rbp1 , which regulates retinoic acid (RA) homeostasis, and that is silenced in more than 40% of PCs [ 63 ]; Shbg , which regulates testosterone metabolism and supports cell growth [ 64 ]; and Tmprss2 , a membrane-anchored serine protease involved in PC progression, which can be found as TMPRSS2-ERG fusion gene in about 50% of PCs [ 65 ], and Vegfa , which promotes angiogenesis and metastasis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…ING4 expression is lost in more than a half of human primary prostate malignancies [2]. Moreover, ING4 loss is tightly correlated with loss of another tumour suppressor, PTEN, and associated with a dysfunctional differentiation program of basal epithelial cells resulting in prostate tumorigenesis [2,3]. Both malignant tissues isolated from PC patients and PC cell lines demonstrate decreased ING5 expression when compared to the non-malignant control [4].…”
Section: Ing Expression Levels In Pcmentioning
confidence: 99%